2021
DOI: 10.1002/dc.24904
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the use of the ACR‐TIRADS as a screening tool for thyroid nodules in a cancer center

Abstract: Background: The Thyroid Imaging Reporting and Data System (TIRADS) was created to assess risk of thyroid nodules through ultrasound. Plenty classifications methods for thyroid nodules have already been created, but none of them have yet achieved global utilization. This study analyzed the performance of the American College of Radiology (ACR) TIRADS, its reproducibility and the impact of its utilization as a screening method in a large Cancer Center cohort.Methods: Thyroid nodules which underwent fine-needle a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…The current study showed an increased malignancy risk with an increasing nodule's ACR-TIRADS level. This comes in line with the studies done by Qi et al (27) and Araruna et al (28) in which a significant trend of a rising malignancy risk was noted as the final TR risk level gradually increased from TR1 to TR5.…”
Section: Discussionsupporting
confidence: 91%
“…The current study showed an increased malignancy risk with an increasing nodule's ACR-TIRADS level. This comes in line with the studies done by Qi et al (27) and Araruna et al (28) in which a significant trend of a rising malignancy risk was noted as the final TR risk level gradually increased from TR1 to TR5.…”
Section: Discussionsupporting
confidence: 91%
“…The aim of this study has been to evaluate the diagnostic performance of ACR TI-RADS scoring systems that have cytology and histology as reference. Taking into account the former, ACR TI-RADS showed a comparable performance in terms of RON as previously reported [ 22 ]. In fact, a significant trend towards an increase of RON was observed in ACR TI-RADS when going from the lower- to the higher-risk categories, in line with what was previously described in the current literature, and, in particular, about the initial ACR TI-RADS white paper [ 23 ].…”
Section: Discussionsupporting
confidence: 81%
“…Of the 951 articles identified via the database search, 35 met eligibility criteria (Figure 1). 18–52 We found that the inter‐rater reliability amongst independent reviewers for the abstract screening and full‐text review stages was 0.704 (95% CI: 0.628, 0.781) and 0.766 (95% CI: 0.630, 0.903), respectively.…”
Section: Resultsmentioning
confidence: 92%